Проблеми співвідношення кримінально-правового впливу та покарання - Яцишин, Михайло Михайлович; Крисюк, Юрій Петрович; Yatsyshyn, Mykhailo M.; Krysiuk, Yurii P. (Східноєвропейський університет імені Лесі Українки, 2018)
У статті розглядається співвідношення кримінально-правового впливу та покарання. Наголошується на тому, що не дивлячись на активне осмислення кримінально-правового впливу, залишаються невирішеними найбільш принципові його моменти або мають місце доволі розбіжні підходи, що не сприяє розумінню соціального та кримінально-правового його значення.

The article deals with the correlation of criminal influence and punishment. It is noted that despite an active reflection on the criminal influence, its most fundamental aspects remain unresolved or there are quite different approaches that do not contribute to an understanding of its social and criminal law value. First of all, it concerns the lack of unity in the understanding of the essence and concept of criminal influence, its content, boundaries, mechanism and methods of implementation. In the domestic criminal legislation there is no definition and a clear system of measures of criminal legal influence, which complicates the process of their application. The coordination of the positions of scientists is necessary for the development of a sound concept that would explain the logical construction of the system of measures of criminal influence, the mechanism of interaction of its components; the features of the subject of criminal influence are taken into account. In criminal law, a single flexible system of criminal law measures should be fixed, if possible outline clearly to their concept, a single punitive essence, which unites them into a system, integrative goals and general principles. One should formulate, in accordance with existing priorities, general and special rules for the definition of these measures, as well as the procedure, conditions and limits for the application of each of them.
Problems of correlation of criminal influence and punishment
Keywords: кримінальна відповідальність; кримінально-правовий вплив; злочин; злочинність; покарання; criminal liability; criminal law; crime; punishment